2020
DOI: 10.4081/reumatismo.2020.1308
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of serum interferon alpha in Egyptian patients with systemic lupus erythematosus and evaluation of its effect on disease activity: a case-control study

Abstract: Much evidence highlighted the role of interferon alpha (IFN-α) in systemic lupus erythematosus (SLE) and suggested its possible role in assessing disease activity. We measured serum IFN-α in Egyptian SLE patients in order to determine a cutoff value that can be used to distinguish patients from healthy controls and explored its clinical value in monitoring disease activity and different aspects of the disease, in particular lupus nephritis. This cross-sectional, case-control study was conducted on 59 SLE patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The IFN-α serum levels were not associated with SLEDAI. This result goes with what was reported formerly, that IFN-α had no role with the disease activity [31]. Contrast results were found in various studies that reported the significant association between IFN-α serum levels and SLEDAI [39][40][41].…”
Section: P=0245 P =0637supporting
confidence: 86%
See 2 more Smart Citations
“…The IFN-α serum levels were not associated with SLEDAI. This result goes with what was reported formerly, that IFN-α had no role with the disease activity [31]. Contrast results were found in various studies that reported the significant association between IFN-α serum levels and SLEDAI [39][40][41].…”
Section: P=0245 P =0637supporting
confidence: 86%
“…Contrast results were found in various studies that reported the significant association between IFN-α serum levels and SLEDAI [39][40][41]. The laboratory investigations in total showed an insignificant correlation with IFN-α, similar conflicting results were described [31,33]. The negative correlation observed in the current study between hematological parameters that include WBCs count, Hb level and IFN-α, may provide further evidence for the suggestion said leucopenia and anemia could be connected to chemokines [42] and adhesion particles that drive lymphocytes out of the vascular space and increase leukocytes adhesion to vessel wall [43].…”
Section: P=0245 P =0637mentioning
confidence: 59%
See 1 more Smart Citation
“…При этом в дебюте заболевания пациентам с юСКВ назначалась более высокая доза ГКС, что говорит о том, что интерфероновый механизм развития СКВ в разной степени представлен при юСКВ и вСКВ. Это определяет различную активность СКВ с разным возраст-ным дебютом и разный коморбидный профиль взрослых пациентов, заболевших до и после 18 лет [16].…”
Section: Discussionunclassified
“…IFN-α was an important pathogenic factor in the occurrence and development of LN. Although it was elevated in the serum of patients, it could not be used as a biomarker of disease activity [57]. Current IFN-α monoclonal antibodies include sifalimumab, rontalizumab, anifrolumab, IFN-α-kinoid and ASG-009.…”
Section: Interferon Inhibitorsmentioning
confidence: 99%